Nitrogen Fertilizer Driven Bacterial Community Structure in a Semi-Arid Region of Northeast China - Meng Wang (MDPI AG, 2021)
The soil nitrogen (N) cycle is an essential role of the biogeochemical cycle. Bacteria play an irreplaceable part in the soil N cycle, but the impact of different N gradients on bacterial communities remains unclear. The purpose of this research was to explore the bacterial abundance, community composition, and diversity under different N application rates in a water-limited area. We investigated the bacterial abundance, diversity, community composition, and structure under five different N gradients (0, 90, 150, 210, and 270 kg ha−1) using real-time quantitative PCR and high-throughput sequencing, and then explored bacterial functional groups with FAPROTAX. N application significantly affected bacterial abundance and community composition. Bacterial diversity was enhanced at low N application rates and reduced at higher N application rates. Principal coordinate analysis showed that bacterial community structure was separated into two groups between low N application rates and high N application rates; these differences in bacterial community structure may be driven by available nitrogen (AN). The results of FAPROTAX revealed that N application promoted the functions of Aerobic_nitrite_oxidation, Nitrate_reduction, and Aerobic_ammonia_oxidation, but inhibited the Nitrogen_fixation function of the bacterial community. The high N network caused the reduction of network structure stability. Our results revealed that N fertilizer driven bacterial community structure and soil nutrients were the main influential factors in the variation of bacterial community structure. We suggest that the optimal N application rate in this study may be approximately 150 kg ha−1, based on the variations of soil properties and bacterial community structure in semi-arid areas.